Pembelajaran Ansambel Musik di SMPN 1 Banjarnegara - Ismail . (Saraswati)
The ensemble music still be problems in various school.The tendency of the influence of the kids, teachers and school.These studies on the process of ensemble music in smpn 1 banjarnegara a qualitative accompanied by means of observations and interviews as instruments.The study concludes that the ensemble music for self-improvement and gave the students to recognize and cooperate in ensemble music. Keyword: Learning, ensemble music, junior high school